Behavioral Economics: An Analysis from Interdisciplinarity and Complexity - Pérez Martínez, Armenio; Rodríguez Fernández, Aimara (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The article analyzes several assumptions of behavioral economics, to contribute to its  application and theoretical understanding. The research is pure basic, documentary and exploratory. The main theoretical references of behavioral economics are analyzed through the hypothetical-deductive method. A logical-epistemic-prospective study of the knowledge built in behavioral economics and possible further advances is carried out. The research points out the need to complement the limited rationality perspective, analyzes the dual system of reasoning (SDR) and focuses on experimentation as a way to generate new knowledge. The conclusions promote the understanding of rationality from an interdisciplinary and complex vision, with components such as cognitive potential, optimization of results, sufficient information, and control. The SDR is considered to be complex, where reflexive and self-control elements make the response speed slower. These considerations generate new opportunities for analysis and reflection on the psychosocial determinants of the behavior of economic agents.